Alone in Publand: Leaving Academics to Themselves - Mosser, Gianna F.; Wohl, Hannah; Fine, Gary Alan (The American sociologist, 2016)
In recent decades, the number of print and electronic outlets for scholarly publication across the humanities and social sciences has grown exponentially. Business models have shifted from university presses who offer subject-based clusters of journals to include commercial publishers and open-access digital platforms. With greater pressure than ever to publish early and often for those on and just out of reach of the tenure track, concerns with the timeline to publish and the number of outlets for publication become tantamount to the texts themselves. But what happens to the literature? When does readability no longer remain a commitment an author makes to its audience or editors make to their authors? This article argues for a persistent renewal of the journal editor's commitment to providing authors with substantive peer review and suggestions for workable revisions. Publishers of scholarly content should also renew their commitment to professional copyediting in order to create lasting contributions to sociological literature that can be digested, interpreted, and built upon by researchers and students alike.